Neurotoxicity of a polybrominated diphenyl ether mixture (DE-71) in mouse neurons and astrocytes is modulated by intracellular glutathione levels - Giordano, Gennaro (2008)
Polybrominated diphenyl ether (PBDE) flame retardants have become widespread environmental contaminants. Body burden in the U.S. population has been shown to be higher than in other countries, and infants and toddlers have highest exposure through maternal breast milk and household dust. The primary concern for adverse health effects of PBDEs relates to their potential developmental neurotoxicity, which has been found in a number of animal studies. Information on the possible mechanisms of PBDE neurotoxicity is limited, though some studies have suggested that PBDEs may elicit oxidative stress. The present study examined the in vitro neurotoxicity of DE-71, a penta-BDE mixture, in primary neurons and astrocytes obtained from wild-type and Gclm knockout mice, which lack the modifier subunit of glutamate-cysteine ligase and, as a consequence, have very low levels of glutathione (GSH). These experiments show that neurotoxicity of DE-71 in these cells is modulated by cellular GSH levels. Cerebellar granule neurons (CGNs) from Gclm (−/−) mice displayed a higher sensitivity to DE-71 toxicity compared to CGNs from wild-type animals. DE-71 neurotoxicity in CGNs from Gclm (+/+) mice was exacerbated by GSH depletion, and in CGNs from both genotypes it was antagonized by increasing GSH levels and by anti-oxidants. DE-71 caused an increase in reactive oxygen species and in lipid peroxidation in CGNs, that was more pronounced in Gclm (−/−) mice. Toxicity of DE-71 was mostly due to the induction of apoptotic cell death. An analysis of DE-71-induced cytotoxicity and apoptosis in neurons and astrocytes from different brain areas (cerebellum, hippocampus, cerebral cortex) in both mouse genotypes showed a significant correlation with intracellular GSH levels. As an example, DE-71 caused cytotoxicity in hippocampal neurons with IC50s of 2.2 and 0.3 µM, depending on genotype, and apoptosis with IC50s of 2.3 and 0.4 µM, respectively. These findings suggest that the developmental neurotoxicity of PBDE may involve oxidative stress, and that individual with genetic polymorphisms leading to lower GSH levels may be more susceptible to their adverse effects.